Gender violence and the construction of new gender identities: Roma migrant women’s lived experiences in Romania and Spain - Jupineant Cioran, Adriana; Cretan, Remus; Voiculescu, Sorina; Alcañiz Moscardó , Mercedes (Geographica Pannonica, 2023)
Recent research indicates that there are critical physical, psychological, verbal and economic issues that shape the types of violence to which women are subject. This study analyses how Roma migrant women fall victim to domestic abuse, both in their home country (Romania) and abroad (Spain). Drawing on literature regarding violence against women, a survey (N=132) was conducted with Romanian Roma migrant women in Spain to understand the ways in which they reconstructed their gender identities in the face of violence. Further semi-structured interviews were undertaken with five Roma migrant women to determine the ways in which these women perceived the forms of violence to which they fell victim, what caused their partners to become perpetrators, and what roles their own families played in this scenario. The findings of our study reveal the inherent insecurities that violence has inflicted on our participants, unmask the destructive effects on the family unit, and explain how some of the interviewees were able to transcend their experience and initiate a process of resetting their gender identities. If the predominance of the traditional patriarchal structure of Roma society can be observed during the life experiences of the Roma women in Romania, the gender characteristics are changing among those Roma women who have migrated to Spain: there is a greater emphasis on a fairer distribution of domestic tasks, decision-making in the family, and their ability to adapt to new possibilities for professional development. The study concludes that although violence against Roma women is still a real issue in Spain, women are re-defining their gender identities to resist traditional patriarchal structures.